NAVIGATING THE NEW NORMS: AN HR LEADER'S GUIDE TO DEI, WELL-BEING, AND FLEXIBLE WORK - Ari Fitriany; Oktavianti; Rizki Eka Putra (RADJA PUBLIKA, 2026)
The contemporary workplace is undergoing a fundamental transformation, driven by post-pandemic expectations, social justice movements, and a heightened focus on holistic employee value. This research investigates the complex interplay between Diversity, Equity, and Inclusion (DEI), employee well-being, and flexible work models as the three pillars of the